Multivariate analysis of factors associated with Schistosoma mansoni and hookworm infection among primary school children in rural Bahir Dar, Northwest Ethiopia - Tadesse Hailu (Tropical Diseases, Travel Medicine and Vaccines, 2018)
Abstract Background Soil-transmitted helminths and Schistosoma mansoni infections are the major causes of morbidity and mortality in Sub-Saharan countries. The highest burden of the disease resides in school-age children. Poor water sanitation and hygiene are believed to be the major contributing factors for the high prevalence. Therefore, the goal of this study was to determine the prevalence of intestinal parasite infections in rural Bahir Dar, Northwest Ethiopia. Methods A cross-sectional study was conducted from April 2017–June 2017 among 409 randomly selected primary school children. A structured questionnaire was used to obtain socio-demographic information and determinant factors through interviewing the students. Stool examination was done by Ritchie’s concentration method. The data were entered and analyzed using SPSS version 22. Prevalence of helminthic infections was calculated using descriptive statistics. The association between helminthic infection and determinant factors was determined by Bavarian regression. The confounding effect was checked by multivariate regression at 95% confidence interval. Any association was significant when the p-value was < 0.05. Result The overall prevalence of intestinal parasite infection was 47.2%.(193/409).. The prevalence of Hookworm species and Schistosoma mansoni was 31.1 and 8.0%, respectively. Co-infection of Hookworm species with Schistosoma mansoni was 5.1% (21/409). The highest prevalence of Schistosoma mansoni was recorded for boys (21%), older children (21.4%) and rural children (17.6%) (P < 0.05). Schistosoma mansoni infection was also higher among children whose household drinking water was sourced from streams/rivers (P < 0.05). The multivariate analysis showed lower odds of Schistosoma mansoni infection for those with no history of bathing (AOR = 3.7, 95% CI: 1.1–12.2; P = 0.034), washing clothes/utensils (AOR = 3.4; 95% CI: 1.2–9.7; P = 0.022), swimming (AOR = 2.8, 95% CI: 1.2–6.9; P = 0.023), and irrigation (AOR = 2.8, 95% CI: 1.3–6.0; P = 0.01). Significantly, higher odds of Hookworm infection was recorded for older children (AOR = 2.3, 95% CI: 1.08–4.89; P = 0.029), boys (AOR = 1.9, 95% CI: 1.12–3.24; P = 0.018), and rural children (AOR = 1.8, 95% CI: 1.04–3.0; P = 0.037). Regular shoe wearing (AOR = 0.29, 95% CI: 0.16–0.50; P = 0.00) is protective for hookworm infection. Higher odds of hookworm infection was also recorded for schoolchildren who had the habit of eating raw vegetables (AOR = 1.2 95% CI: 1.1–1.7 P = 0.011). Conclusion Hookworm infection and schistosomiasis are prevalent in the school children in rural Bahir Dar in Northwest Ethiopia. Various activities and behaviors of the children were strongly associated with helminthic infection. Hence health education should be delivered regularly to minimize/avoid the risky behaviors and water-based activities. Deworming programs should also be implemented on a regular basis.